Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Pelanggan Biznet Network Kota Jakarta Utara (Jurnal Manajemen Kreatif dan Inovasi, 2025)
In today’s digital era, the demand for fast, stable, and affordable internet services continues to grow alongside the rapid advancement of communication technology. Biznet Network, as one of the leading internet service providers in North Jakarta, is required to deliver optimal service quality and competitive pricing in order to maintain customer loyalty. This study aims to examine and analyze the influence of service quality and price on customer loyalty toward Biznet Network. The research employed a descriptive quantitative method with a sample of 100 respondents selected using purposive sampling from the population of Biznet customers in North Jakarta. Data were collected through observation, interviews, and questionnaires using a Likert scale, and then analyzed using validity and reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The findings reveal that service quality (X₁) has a significant negative effect on customer loyalty (Y), with a calculated t-value of -2.270 greater than the critical t-table value of 1.984, indicating that a decline in service quality leads to decreased customer loyalty. Similarly, price (X₂) has a significant negative effect on customer loyalty, with a calculated t-value of -2.023 > 1.984, suggesting that unfavorable pricing perceptions reduce loyalty. The F-test results show that service quality and price simultaneously have a significant effect on customer loyalty, with an F-value of 7.686 > 3.09 and a significance level of 0.001 < 0.05. The R² value of 0.137, or 13.7%, indicates that these two variables explain customer loyalty, while the remaining 86.3% is influenced by other factors not examined in this study.